Determinant of Early Initiation of Breastfeeding in a Tertiary Neonatal Unit - Nepal, Deepeshwara; Jeeva, Sankar M; Misra, Satish M; Paul, Vinod K (Journal of Nepal Paediatric Society, 2009)
Introduction: Initiation of breastfeeding within one hour of birth is an important determinant of successful breastfeeding. National Family and Health Survey -3(NFHS-3) reported that only 23.4% of children < 3 years were breastfed within one hour of birth. Objectives: the purpose of this study is to study the determinant of initiation of breastfeeding within one hour of birth. Setting: Tertiary -level neonatal unit. Material and Methods: All mothers admitted in the postnatal ward were eligible for inclusion; mothers of sick and /or preterm infants were excluded. Enrolled mothers were interviewed between 24 and 72 hours after delivery. Results: The proportion of mothers who initiated breast feeding within one hour of delivery was 32%, between 1-6 hrs were 47% and between 6 to 48 hrs were 21%. Maternal age, education, socioeconomic status, occupation and antenatal or labor room counseling did not influence the initiation of breast feeding within one hour of delivery in univariate analysis. On multivariate analysis, admission in the general ward and delivery by caesarean section were found to be significantly associated with not initiating breastfeeding within one hour (adjusted ORs: 8.79, 2.48 to 31.08, p=0.001 and 6.79, 4.07 to 22.02 p=0.001 respectively). Only about 13% of the infants received prelacteal feeds. Conclusion: Mothers delivering by caesarean section or admitted in the general ward were at high risk of not initiating breastfeeding within one hour. Innovative strategies are required to ensure timely ignition of breastfeeding. Key words: Breastfeeding, Caesarean section, prelacteal feeds, time of initiation. doi: 10.3126/jnps.v29i2.2042 J. Nepal Paediatr. Soc. Vol 29, No. 2, pp.74-78